Forensic Audit Practice and Occurrence of Fraud in Public Sector Organization: A Study of University of Douala, Cameroon - Prosper, Kengne Fotsing; Sama, Prof. Molem Christopher; Egbe, Prof. Ebai John (Law and Economy, 2025)
The study examined forensic audit practice and occurrence of fraud in public sector organization. A study of University of Douala, Cameroon. The specific objectives were to: examine the effect of substantive technique on fraud control, determine the effect of statistical principle on fraud control and to ascertain the effect of data mining application on fraud control. The study adopted primary sources of data using questionnaire instruments. Ordinary least square of multiple regression was adopted in this study. The major findings revealed thus: there was a significant effect of substantive technique on fraud control, there was a significant effect of statistical principle on fraud control and data mining application had a significant effect on fraud control. On the basis of these findings, the study recommended; thus, Eradication of economic and financial crime through the adoption of forensic accounting in the system will improve the image of university under review. Also, detection and prevention of corruption have given rise to the profession of forensic accounting. Due to this fact, the most important thing University has to do with regard to fraud is to prevent crime from being committed. Finally, government and regulatory authorities should ensure the provision of standards and guidelines to regulate forensic activities and above all educational sectors should embrace integrity, objectivity, fairness and accountability in their day-to-day activities.